An online Arabic vocabulary learning games prototype - Sahrir, Muhammad Sabri (2010)
This is an online Arabic vocabulary learning games prototype which is specifically designed for elementary learners at pre-university level at Centre for Foundation Studies (CFS), International Islamic University Malaysia (IIUM). It allows the students to use it as an additional learning aid to learn Arabic language in a gaming application. It provides a new learning experience for them who have been through a traditional Arabic teaching and learning methods, by immersing into the attractive, interesting and interactive game-based learning environment.